Asymmetric pseudo-capacitors based on dendrite-like MnO2 nanostructures. Issue 21 (16th May 2019) - Zhao, Yue; Dai, Meizhen; Zhao, Depeng; Xiao, Li; Wu, Xiang; Liu, Fei
Abstract : Dendrite-like MnO2 nanostructures grown on carbon cloth are successfully prepared by a facile one-step route. Abstract : Dendrite-like MnO2 nanostructures grown on carbon cloth are successfully prepared by a facile one-step route. The as-prepared nanoarchitecture delivers a specific capacity of 430 F g −1 at 1 A g −1 and excellent cycling stability. In addition, a quasi-solid-state asymmetric supercapacitor is assembled by using the dendrite-like MnO2 nanostructures as the positive electrode. It shows an energy density of 20.65 W h kg −1 at a power density of 437.30 W kg −1 at a voltage window of 2.45 V. The results reveal that the as-synthesized MnO2 products might be promising electrode materials for electrochemical energy storage.